2022
DOI: 10.1111/ans.17666
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy of endoscopic pilonidal sinus treatment: a single‐centre Australian experience

Abstract: Background Endoscopic pilonidal sinus treatment (EPSiT) is a novel minimally invasive technique for treating pilonidal sinus disease (PSD) involving endoscopic assessment and treatment. This retrospective, non‐randomized, observational study is the first Australian study of EPSiT and its largest long‐term study to date. Methods From January 2014 to November 2019, 137 patients with PSD underwent EPSiT. Seventy‐two had undergone previous surgery for PSD. Specialized Karl Storz video equipment (fistuloscope) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to the latest Italian guidelines, EPSiT technology is regarded as the gold standard for the treatment of PS diseases 112 . In the latest study, which is the first single-centre retrospective study in Australia, 13.5% of patients experienced post-healing recurrences after an average follow-up of 56.2 months 113 . In another retrospective study with a median follow-up of 49 months and a mean postoperative follow-up of 19 months, the postoperative recurrence rate was 15%.…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest Italian guidelines, EPSiT technology is regarded as the gold standard for the treatment of PS diseases 112 . In the latest study, which is the first single-centre retrospective study in Australia, 13.5% of patients experienced post-healing recurrences after an average follow-up of 56.2 months 113 . In another retrospective study with a median follow-up of 49 months and a mean postoperative follow-up of 19 months, the postoperative recurrence rate was 15%.…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 4 IDEAL checklists for IDEAL Stages 2a and 2b Milone [28] Milone [52] Milone [22] Esposito [31] Esposito [30] Dotlacil [53] Pérez-Bertólez [64] Gulcu [27] Meinero [29] Chia [40] Gecim [49] Sequeira [21] Pini Prato [55] Khafagy [56] Romaniszyn [23] Gökbuget [39] Giordano [42] Gallo [59] Yuksel [33] Baxter [34] Javed [20] Jain [63] Stage Manigrasso [26] Manigrasso [35] Esposito [32] Esposito [24] Esposito [25] Meinero [37] Giarratano [54] Meinero [38] Mendes [41] Kalaiselvan [57] Azhough [58] Foti [60] Gulcu [61] Hinksman [62] A prospective multicentre trial showed a quick postoperative recovery and a good quality of life after EPSiT [37]. A prospective international multicentre study on 122 patients with recurrent PD showed a complete wound healing in 95% of patients, within a mean time of 29 days.…”
Section: Outcomes Of the Techniquesmentioning
confidence: 99%